Ozone ultrafine bubble water sterilizes Porphyromonas gingivalis and neutralizes its virulence factors - Mana Endo; Hisanori Domon; Satoru Hirayama; Fumio Takizawa; Akiomi Ushida; Koichi Tabeta; Yutaka Terao (PLoS ONE, 2025)
Periodontitis is caused by Gram-negative bacteria. Porphyromonas gingivalis, a major Gram-negative periodontal pathogen, produces virulence factors such as gingipains, lipopolysaccharide (LPS), and lipoproteins, which contribute to tissue destruction. Ozone ultrafine bubble water (OUFBW) has been studied for its antimicrobial effects against various bacteria and toxin protein inactivation. This present study aimed to explore the effects of OUFBW on P. gingivalis and its virulence factors. OUFBW was generated and applied to P. gingivalis to assess bactericidal activity. OUFBW effects on morphological changes in P. gingivalis and its membrane vesicles (MVs) were analyzed using transmission electron microscopy. Gingipain activities in OUFBW-treated P. gingivalis culture supernatant was tested using fluorogenic substrates and endogenous substrates, E-cadherin and IL-6. Degradation of OUFBW-treated gingipains was analyzed by silver staining and western blotting. Effects of OUFBW on P. gingivalis lipoproteins and LPS were evaluated using HEK-Blue cells expressing Toll-like receptor 2 (TLR2) and TLR4, respectively. Cytotoxicity of OUFBW on human gingival cells was analyzed using an MTT assay. OUFBW disrupted the inner membrane of P. gingivalis, leading to elimination of the bacterium and reduction of MVs. OUFBW also decreased gingipain activities and inhibited gingipain-induced degradation of E-cadherin and IL-6 due to gingipain breakdown. Additionally, OUFBW suppressed lipoprotein-induced TLR2 activation but had no effect on LPS-mediated TLR4 signaling. OUFBW showed low cytotoxicity in human gingival cells. Our findings indicate that OUFBW can sterilize P. gingivalis and inactivate gingipains and lipoproteins. These results suggest that OUFBW would be used to disinfect periodontal treatment instruments.